2020
DOI: 10.1111/crj.13146
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema is associated with the aggressiveness of COPD‐related adenocarcinomas

Abstract: Objectives To compare the differences in radiologic and pathologic features of surgically resected chronic obstructive pulmonary disease (COPD)‐related adenocarcinomas according to the presence of emphysema. Methods A total of 216 smokers with surgically resected lung adenocarcinoma were included in this retrospective study, and 102 patients were diagnosed with COPD. We classified COPD patients as emphysematous or non‐emphysematous group based on the emphysema severity on computed tomography (CT) and evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…[40][41] Previous research has con rmed that LUAD accompanied by emphysema exhibits more aggressive characteristics and lower disease-free survival rates compared to cases without emphysema. [42][43] Consistently, our study indicated that LUAD with emphysema is more prone to invade the visceral pleura. 44 The solid component size re ects the invasiveness of the tumor itself, while the other features re ect the relationship between the tumor and the adjacent pleura, vessels, and pulmonary background.…”
Section: Discussionsupporting
confidence: 82%
“…[40][41] Previous research has con rmed that LUAD accompanied by emphysema exhibits more aggressive characteristics and lower disease-free survival rates compared to cases without emphysema. [42][43] Consistently, our study indicated that LUAD with emphysema is more prone to invade the visceral pleura. 44 The solid component size re ects the invasiveness of the tumor itself, while the other features re ect the relationship between the tumor and the adjacent pleura, vessels, and pulmonary background.…”
Section: Discussionsupporting
confidence: 82%
“…This traction results in morphological changes in nearby bronchi, vessels, and pleura, which manifest as air bronchogram signs, vascular convergence signs, and pleural indentation signs on CT images [43,44]. Previous research has confirmed that LUAD accompanied by emphysema exhibits more aggressive characteristics and lower disease-free survival rates compared to cases without emphysema [45,46] Consistently, our study indicated that LUAD with emphysema is more prone to invade the visceral pleura [47]. The solid component size reflects the invasiveness of the tumor itself, while the other features reflect the relationship between the tumor and the adjacent pleura, vessels, and pulmonary background.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have shown that quantitative emphysema severity of the whole lung and stage III were independent predictors of lung cancer recurrence after adjusting for age, gender, smoking status, and FEV1 ( 46 ). Lung adenocarcinomas in the emphysema group have a more aggressive pathologic grade and a higher prevalence of solid lesions ( 47 ). Consistent with previous studies, our study showed that emphysema was also independently associated with lung cancer coexisting with COPD.…”
Section: Discussionmentioning
confidence: 99%